Caring For, About, and With: Exploring Musical Meaningfulness Among Suzuki Students and Parents - Hendricks, Karin S.; Einarson, Kathleen M.; Mitchell, Nancy; Guerriero, Elizabeth M.; D’Ercole, Patricia (Frontiers in Education, 2021)
An investigation of the relationships between empathy, music learning, and shared musical values may provide new insights into the ways that musical meaningfulness and the symbiotic eudaimonic ideal—“flourishing of oneself and of others”—might be cultivated. We investigated the relationships between parent perceptions of children’s empathy, parent beliefs and values about music, and formal Suzuki training over a period of six months, to understand ways in which shared music learning experiences might relate to emotional and musical connections between parents and children. Participants were parents of 48 Suzuki students at a structured Suzuki school in the Midwestern United States. We designed a survey containing an adapted version of the Griffith Empathy Measure for children with additional questions regarding family demographics and values regarding music education. Participants completed the survey at the start of the lesson year, and again six months later. Children who persisted in group lessons throughout the study began with significantly higher empathy scores, compared to those children who did not participate in group lessons. Children’s initial empathy scores were significantly positively correlated with parents’ ratings of the importance of music instruction generally, and of Suzuki instruction particularly, to their family. A significant but moderate correlation was found between initial empathy scores and the belief that music would help the child succeed in other areas. This exploratory study highlights potential relationships between parents’ musical values, children’s empathy, and participation in group music-making. Our findings are consistent with research demonstrating that child and parent personalities predict the duration of formal music training for children. They also support the philosophy of musical meaningfulness proposed by Silverman, by suggesting ways in which meaningful connections may be forged simultaneously between people who care for one another, and between people and the activities they care about. Our results point to the importance of providing a variety of music learning activities and structures that reflect the personality, needs, and interests of children and parents. We offer specific recommendations for future research to draw further insights and implications about these relationships.